Karakteristik Pekerjaan pada Kasus Human Immunodeficiency Virus-1 dan Subtipenya di Tujuh Provinsi di Indonesia pada tahun 2011 - Roselinda, Roselinda; Wibowo, Holy Arif; Setiawaty, Vivi (Jurnal Biotek Medisiana Indonesia, 2015)
Abstract HIV-1 sociodemographic factors and distribution are different among regions. Some jobs are at risk for contracting the disease. The purpose of the analysis is to look at the characteristics of the occupation in the case of HIV-1 in several provinces in Indonesia. Data were analyzed based on a survey of HIV-1 virus genotypes in 7 provinces in Indonesia in 2011. Respondents were selected purposively from cases of HIV / AIDS who visited the clinic Voluntary Care and Treatment (VCT) in seven provinces (North Sumatra, West Sumatra, Kepulauan Riau, South Sulawesi, North Sulawesi, Maluku and Papua). Data and specimen were collected by conducting laboratory examination and also interviews wearing a structured questionnaire. The highest proportion of cases of HIV-1 is the housewife/jobless (50.8%), and the highest is found in Papua province (92,9%). Private sector (13,3%) the highest is in North Sumatra (35,7%), Businessmen (16,9%) the highest is in Riau Island (32,9%), the Labor (11.4%) the highest is in North Sulawesi, Civil worker (3.9%) is the highest in North Sulawesi and Maluku(10%), and sexual workers (3.7%) is the highest in Riau Islands (11,4%). Meanwhile proportion of HIV-1 subtype CRF01-AE cases higher in the male,, in age group 15-30 years, in bachelor education level and in private sector. The housewife and jobless included in this group is a very vulnerable to contracting HIV-1, and it should receive attention in improving knowledge about the disease, gender equality in disease control. Key words: HIV-1, Occupations, Indonesia Abstrak Faktor sosiodemografi HIV-1 dan distribusinya  berbeda antar daerah. Beberapa pekerjaan mempunyai risiko untuk tertular penyakit ini. Tujuan analisis ialah untuk melihat karakteristik pekerjaan pada kasus HIV-1 dan subtipenya pada beberapa provinsi di Indonesia. Data yang dianalisis berasal dari survei genotipe virus HIV-1 di 7 Provinsi di Indonesia tahun 2011. Responden dipilih secara purposif dari kasus HIV/AIDS yang mengunjungi klinik Perawatan Sukarela dan Pengobatan (VCT) di tujuh provinsi (Sumatera Utara, Sumatera Barat, Kepulauan Riau, Sulawesi Selatan, Sulawesi Utara,Maluku, dan Papua). Data dan spesimen dikumpulkan dengan melakukan pemeriksaan laboratorium serta wawancara memakai kuesioner terstruktur. Proporsi terbanyak kasus HIV-1 adalah kelompok ibu rumah tangga/tidak mempunyai pekerjaan (50,8%), dan jika dilihat per propinsi ditemukan tertinggi di Papua (92,9%).  Wiraswasta (13,3%) tertinggi Sumatera Utara (35,7%), swasta (16,9%) tertinggi di Kepulauan Riau (32,9%),  buruh (11,4%)  tertinggi di Sulawesi Utara (18,6%), pegawai negri sipil (3,9%) tertinggi di Sulawesi Utara dan Maluku (10%), dan wanita penjaja seks (3,7%) tertinggi di Kepulauan Riau (11,4%). Sementara proporsi kasus HIV-1 subtipe CRF01-AE lebih banyak pada kelompok laki-laki, umur 15-30 tahun, berpendidikan akademi dan pekerjaan wiraswasta. Kelompok ibu rumah tangga dan tidak bekerja termasuk kedalam kelompok ini merupakan kelompok yang sangat rentan tertular penyakit HIV-1, perlu mendapat perhatian peningkatan pengetahuan tentang penyakit dan kesetaraan gender dalam pengendalian penyakit. Kata kunci: HIV-1, Pekerjaan, Indonesia